DEVELOPMENT OF INDONESIA CULTURAL LADDER SNAKE MEDIA TO IMPROVE LEARNING OUTCOMES OF GRADE III PRIMARY SCHOOL IPAS: Pengembangan Media Ular Tangga Budaya Indonesia Untuk Meningkatkan Hasil Belajar IPAS Kelas III SD - Galuh Kartika Dewi; M. Khusni Mubarok; Alviera (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research aims to design and develop a learning media in the form of snakes and ladders with an Indonesia Culture theme, with the learning outcomes of IPAS third-grade students. This meddia is designed to overcome low student participation and difficulty in understanding Indonesia cultural material. The research was conducted with a Research and Development (R&D) approach that adopted the ADDIE model Analysis, Design, Development, Implementation, and Evaluation. The data analysis technique use validation tests of media experts, material, validity tests, reliability, and N-gain. The validation reached 85% and material validation 91%, categorized as feasible to use during learning. The validity test results R count > R table 0,344 declared valid and reliability 0,775 declared reliable. The increase in learning outcomes from pretest to posttest, where the initial score of 58,2 to 88, woth a KKTP value set at 80, the acquisition of an N-gain score of 0,71 indicates the effectiveness of learning is included in the high category.